Development and Safety Analysis for Low Concentration Coal-bed Methane Liquefaction Equipment - Hao, Yu (International Journal of Computer Science and Information Technology, 2024)
In this paper, the principle and characteristics of low concentration coal-bed methane liquefaction process in coal mine area were introduced. The safety performance of the liquefaction process was proved by experimentation. According to the experiments, this paper expounded the security measures those we took. The operation results of pilot plant and industrial demonstration device showed it was security to produce LNG by the cryogenic liquefaction technology of the low concentration coal-bed methane. This technology could be widely used in the coal mine areas those were abundance of coal-bed methane. By using the technology, the product purity could reach 99% and the yield of the methane could reach more than 98%.